Why should we write in english? - Rodríguez, Arnulfo (MedUNAB, 2003)
Resumen The Board of Directors of the MedUNAB Journal of Medicine has come, unanimously, to the conclusion that publishing articles, in this Magazine, written in a dfeerent language, other than the traditional Spanish specifically in English is an excellent and proper idea, taking in cosideration that this language has become, since a long time ago, a universal tongue and presently, science is spoken and written in English.